Adaptation of the 5-choice serial reaction time task to measure engagement and motivation for alcohol in mice - Starski, Phillip; Maulucci, Danielle; Mead, Hunter; Hopf, Frederic (Frontiers in Behavioral Neuroscience, 2022)
Alcohol use disorder (AUD) is related to excessive binge alcohol consumption, and there is considerable interest in associated factors that promote intake. AUD has many behavioral facets that enhance inflexibility toward alcohol consumption, including impulsivity, motivation, and attention. Thus, it is important to understand how these factors might promote responding for alcohol and can change after protracted alcohol intake. Previous studies have explored such behavioral factors using responding for sugar in the 5-Choice Serial Reaction Time Task (5-CSRTT), which allows careful separation of impulsivity, attention, and motivation. Importantly, our studies uniquely focus on using alcohol as the reward throughout training and testing sessions, which is critical for beginning to answer central questions relating to behavioral engagement for alcohol. Alcohol preference and consumption in male C57BL/6 mice were determined from the first 9 sessions of 2-h alcohol drinking which were interspersed among 5-CSRTT training. Interestingly, alcohol preference but not consumption level significantly predicted 5-CSRTT responding for alcohol. In contrast, responding for strawberry milk was not related to alcohol preference. Moreover, high-preference (HP) mice made more correct alcohol-directed responses than low-preference (LP) during the first half of each session and had more longer reward latencies in the second half, with no differences when performing for strawberry milk, suggesting that HP motivation for alcohol may reflect “front-loading.” Mice were then exposed to an Intermittent Access to alcohol paradigm and retested in 5-CSRTT. While both HP and LP mice increased 5-CSRTT responding for alcohol, but not strawberry milk, LP performance rose to HP levels, with a greater change in correct and premature responding in LP versus HP. Overall, this study provides three significant findings: (1) alcohol was a suitable reward in the 5-CSRTT, allowing dissection of impulsivity, attention, and motivation in relation to alcohol drinking, (2) alcohol preference was a more sensitive indicator of mouse 5-CSRTT performance than consumption, and (3) intermittent alcohol drinking promoted behavioral engagement with alcohol, especially for individuals with less initial engagement.